2017
DOI: 10.1371/journal.pone.0188331
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and association of metabolic syndrome and vitamin D deficiency among postmenopausal women in a rural block of West Bengal, India

Abstract: BackgroundPrevalence of metabolic syndrome (MS) and vitamin D deficiency was reported among postmenopausal women (PMW) in India. However, no report is available regarding the association of MS and 25-hydroxyvitamin D [25(OH)D] among PMW in India. This study aimed to find out the prevalence of MS and 25(OH)D status as well as their association among rural PMW of West Bengal, India.Materials and methodsThis cross-sectional study was conducted among 222 randomly selected rural PMW in Singur Block, West Bengal, In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 51 publications
1
18
0
Order By: Relevance
“…These studies which included various age groups reflect the magnitude of the problem. High prevalence was seen throughout the country[ 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 ] [ Table 2 ].…”
Section: Magnitude Of Vitamin D Deficiency In Indiamentioning
confidence: 99%
“…These studies which included various age groups reflect the magnitude of the problem. High prevalence was seen throughout the country[ 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 ] [ Table 2 ].…”
Section: Magnitude Of Vitamin D Deficiency In Indiamentioning
confidence: 99%
“…This is similar to 51% prevalence of vitamin D levels <20 ng/ml reported from a study by Srimani et al from West Bengal, but comparatively lower than 84.9% and 92.5% reported in a study from Cuttack and Kolkata. 14,16,29 Our study reported prevalence of vitamin D level <30 ng/ml as 76.3% and <20 ng/ml as 49.3% amongst subjects from west India; which is comparatively lower than the incidence rate of 70% and 87.5% reported in healthy individuals, in studies by Shivane et al and Multani et al from Mumbai. 32,37 In our study, the prevalence of vitamin D level of <30 ng/ml in male and female subjects was 77.3% and 76.5%, respectively; and vitamin D level of <20 ng/ml was 50.1% and 51.2%, respectively.…”
Section: Discussionmentioning
confidence: 55%
“…[2][3][4] In particular, vitamin D levels have been reported to influence the risk of MetS in many studies. 2,[5][6][7] After menopause, it is common to observe low concentrations of vitamin D among women. 8 In addition, postmenopausal women are at high risk of MetS due to a decrease in estrogen levels.…”
Section: Introductionmentioning
confidence: 99%